Procedimento Simples de Diluição de Biodiesel em Álcool para Determinação de Mg Por Espectrometria de Absorção Atômica com Chama - Santos, Wdson Almeida (2016)
This paper proposes a simple alternative method of sample preparation for determination of magnesium in biodiesel by Flame Atomic Absorption Spectrometry (FAAS), using short-chain alcohols for dissolution of biodiesel samples. The ethanolic and propanolic medium allowed the use of aqueous standard without the need for viscosity adjustment in biodiesel samples due to a good instrumental response. The analytical curves were prepared in the concentration range from 0.0 to 1.0 mg L-1, using the acid-alcohol medium and biodiesel/alcohol-acid medium. Sample preparation consisted of dissolving 1 g of biodiesel, 100 μL of concentrated HNO3 and volume measured to 10 mL with ethanol or propanol. The inorganic standard solution of Mg in the biodiesel alcohol/acid medium was stable for three consecutive days at a good analytical signal. In this study the analytical curves in the acid-alcohol and the biodiesel alcohol acid mediums showed a correlation coefficient (R) greater than 0.99 and relative standard deviation (RSD < 20%). The matrix effect was tested by comparing the slopes of analytical curves made in an alcoholic medium (ethanol or propanol) and nitric acid, showing through the t test that the slopes are statistically equal without matrix effect. As for comparison of methods, F and Student t tests were applied, with a confidence level of 95%, and the results were statistically consistent indicating that ethanol or propanol both may be used in the determination of Mg in the biodiesel/alcohol medium by FAAS. The limits of detection (LOD) and quantification (LOQ) using biodiesel dissolving in acidified ethanol was 1.25x10-3 mg L-1 and 4.17x10-3 mg L-1, respectively. The accuracy of the method using biodiesel in the propanol acid medium was also evaluated by addition and recovery and the results for recovery percentages were in the range of 97 - 103%, with relative standard deviation (RSD) lower than 20% and the limits of detection (LOD) and quantification (LOQ) equal to 1.24x10-3 mg L-1 and 4.14x10-3 mg L-1, respectively. These results indicate that the simple sample preparation procedure using ethanol or propanol as the solvent is effective for the determination of Mg in biodiesel by FAAS.